Structural diversity and efficacy of culturable cellulose decomposing bacteria isolated from rice–pulse resource conservation practices. (14th August 2019) - Dash, Pradeep Kumar; Bhattacharyya, Pratap; Shahid, Mohammad; Roy, Pritesh Sunder; Padhy, Soumya Ranjan; Swain, Chinmaya Kumar; Kumar, Upendra; Kumar, Anjani; Gautam, Priyanka; Lal, Banawari; Panneerselvam, Periyasamy; Nayak, Amaresh Kumar
Abstract: The diversity of cellulolytic bacteria from the rice–pulse system can be sourced for identification of efficient cellulose decomposing microbial strains. In the present study, the abundance, structural diversity, and cellulolytic potential of the culturable bacterial community were studied in 5‐year old rice–pulse system under different resource conservation technologies. Higher cellulose (68% more) and xylanase (35% more) activities were observed under zero tilled soil. The populations of cellulolytic bacteria were significantly higher (44%) in zero tillage (ZT) treatment than those of conventional practice. Results revealed that the cellulolytic bacterial diversity was found to be significantly higher under ZT practice, but the present population may not be sufficient for effective recycling of organic wastes in this system. Out of 290 bacterial isolates, 20 isolates had significantly higher cellulolytic activities, of which the top three superior isolates were received from ZT practice. The cellulolytic bacterial diversity based on 16S rDNA sequencing data revealed that the Firmicutes was the most dominant phyla and the Bacillus spp. were the common genus, the observation also showed that there were 17 different haplotypes were recorded among 20 isolates of cellulolytic bacteria. The present findings indicated that long‐term ZT in the rice–pulse system could be a unique source for efficient cellulose decomposing bacteria and further the efficient bacterial strains isolated from this system can be used as efficient bioinoculants for in situ as well as ex‐situ decomposition of rice straw particularly in conservation agriculture.